WSRP : dynamic and real-time integration an introduction to WSRP, its usage and implementation. - Gupta, Rahul Kumar (SOA webservices journal.)
The IT industry has seen various milestones. Some of the major milestones are the introduction of Desktop PCs, Windows platform, C language, the evolution of OOPS and C++, Internet technologies and JAVA. WSRP has all of the necessary characteristics for becoming a member of this elite group. WSRP is an example of real-time integration and it exploits the power of Web services and portlet technologies.